Diâmetros de cônicas: Uma proposta de abordagem no Ensino Médio - Costa, Deodorio Souza da (2019)
The present works objective is the wide and detailed study of thediameter of the conics, an underexplored axis, but with great relevance in the scope of analytical geometry. The topics below present demonstrations and applications of the contents of the conics, by means of the detailed resolution of examples and the application of concepts conjectured during the construction process, through propositions or theorems, with the objective of presenting the main theme in a succinct way and that it will be used by students orMathematics researchers or related areas.